Do household surveys give a coherent view of disability benefit targeting? A multi-survey latent variable analysis for the older population in Great Britain - Ruth Hancock; Marcello Morciano; Stephen Pudney; Francesca Zantomio (University of East Anglia, Health Economics Group (HEG), 2013)
We compare three major UK surveys, BHPS, FRS and ELSA, in terms of the picture they give of the relationship between disability and receipt of the Attendance Allowance (AA) benefit. Using the different disability indicators available in each survey, we estimate a model in which probabilities of receiving AA depend on latent disability status. Despite major differences in design, once sample composition is standardised through statistical matching, the surveys deliver similar results for the model of disability incidence and AA receipt. Provided surveys offer a sufficiently wide range of disability indicators, the detail of disability measurement appears relatively unimportant.
Keywords: C81; I18; I38; 330; disability indexes; disability benefits; multiple surveys